RELASI AKTOR, INSTITUSI DAN LINGKUNGAN KEBIJAKAN PUBLIK : ANALISIS KEBIJAKAN PENDIDIKAN ANTIKORUPSI - Tatang Sudrajat (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
Currently, corruption has reached an alarming level, because it has penetrated various sectors of life which are very detrimental to state finances. Education is expected to be able to provide mental provisions for students not to commit corruption. The aspect of prevention is relevant in addition to being important as well as the importance of eradicating corrosion. Various state or government policies have been published as efforts to prepare the nation's young generation who are ready to ward off corruption. In this context, public policies have been issued in the form of Law Number 20 of 2003, Presidential Decree Number 87 of 2017, Ministry of Education and Culture Regulation Number 20 of 2018, Governor of West Java Regulation Number 60 of 2019 and Perbup Sukabumi Number 62 of 2019 which pay great attention to integrity, character and education. anti Corruption. Substantial aspects of policy settings on anti-corruption education will determine its success when implemented. With the normative juridical research method and literature review, from the perspective of administration and public policy it appears that in West Java Province the operational policy of the West Java Governor Regulation Number 60 of 2019 and the Sukabumi Regent Regulation Number 62 of 2019 has been issued. policies with policies and hierarchical relationships with policies on anti-corruption education at the national level. Regulation as a form of public policy set in West Java and Sukabumi Regency plays a strategic role in realizing efforts to eradicate corruption.